2022
DOI: 10.3389/fcimb.2022.1006134
|View full text |Cite
|
Sign up to set email alerts
|

Testing Raman spectroscopy as a diagnostic approach for Lyme disease patients

Abstract: Lyme disease (LD), the leading tick-borne disease in the Northern hemisphere, is caused by spirochetes of several genospecies of the Borreliella burgdorferi sensu lato complex. LD is a multi-systemic and highly debilitating illness that is notoriously challenging to diagnose. The main drawbacks of the two-tiered serology, the only approved diagnostic test in the United States, include poor sensitivity, background seropositivity, and cross-reactivity. Recently, Raman spectroscopy (RS) was examined for its LD di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Doty and Ledmev[ 20 ] demonstrated that Raman spectroscopy can be used to identify different animal species from the spectroscopic signatures of their blood. Farber et al [ 21 ] and Goff et al [ 22 ] explored the possibility of using Raman spectroscopy for the detection of Lyme disease from blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…Doty and Ledmev[ 20 ] demonstrated that Raman spectroscopy can be used to identify different animal species from the spectroscopic signatures of their blood. Farber et al [ 21 ] and Goff et al [ 22 ] explored the possibility of using Raman spectroscopy for the detection of Lyme disease from blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…Kurouski and Rogovskyy's groups explored the possibility of using Raman spectroscopy to detect Lyme disease infection from blood samples(Farber et al 2021, Goff et al 2022). …”
mentioning
confidence: 99%